Revisiting Electricity-Economic Growth Nexus in Sub-Sahara Africa: Perspectives from Nigeria and South Africa - OLANRELE, Iyabo (International Journal of Management and Sustainability, 2018)
This study considered the effect of electricity consumption on Nigeria and South Africa's economic growth using Linear Autoregressive Distributed Lag (ARDL) Model. Aside from the size of the two economies and the strategic position they hold in Africa, Nigeria, unlike South Africa, in 2013 reformed its power sector to accommodate private participation for improved performance. In spite of this, the empirical results show that electricity consumption has no significant effect on Nigeria's economic growth both in the short and long-run. Contrarily, there was significant short-run electricity consumption effect on economic growth in South Africa. The effect persisted till the long-run though at an insignificant rate. The implication of the findings is that power sector reforms, especially in 2013, has not brought about the desired economic impact in Nigeria. As such, it is pertinent to revisit and correct the anomalies in the recent power sector privatization for economic growth. Evidently, electricity consumption engenders growth in South Africa, even with recent data, but more investment is required in the power sector to sustain long-run effect on the economy.